Many pathways to literacy young children learning with siblings, grandparents, peers, and communities - Gregory, Eve; Long, Susi 1952-; Volk, Dinah (RoutledgeFalmer, 2004)
"This unique and visionary text is a compilation of fascinating studies conducted in a variety of cross-cultural settings where children learn language and literacy with siblings, grandparents, peers and community members. Focusing on the knowledge and skills of children often invisible to educators, these illuminating studies highlight how children skilfully draw from their varied cultural and linguistic worlds to make sense of new experiences. The vastly experienced team of contributors provide powerful demonstrations of the generative activity of young children and their mediating partners - family members, peers, and community members - as they syncretise languages, literacies and cultural practices from varied contexts. Through studies grounded in home, school, community school, nursery and church settings, we see how children create for themselves radical forms of teaching and learning in ways that are not typically recognised, understood or valued in schools.This book will be invaluable reading for teachers, teacher educators, researchers and policy-makers who seek to understand the many pathways to literacy and use that knowledge to affect real change in schools."